Relationship between imagery use and imagery ability towards team cohesion among MASUM athletes - Dev, Roxana; Siti Yusra, O. D; Tengku Fadilah, T.K.; Soh, Kim Geok; Siswantoyo, . (Human Resource Management Academic Research Society, 2020)
Positive relationship has been determined between imagery use and team cohesion based on individual and team level perspectives from previous studies. However, not many investigated the combination of imagery use and imagery ability on team cohesion from an individual nor from the team perspective especially during the covid-19 pandemic season. Hence, this study investigates the relationship between imagery use and imagery ability on team cohesion among MASUM student athletes. A total of 215 MASUM student athletes from various sports participated in the study. A series of questionnaires were completed which are Group Environment Questionnaire, Sport Imagery Questionnaire-Team Sport and Sport Imagery Ability Questionnaire. Multiple regression analysis revealed that motivation general-mastery imagery, motivation general-arousal imagery, motivational specific imagery, skill imagery ability and goal imagery ability were significantly correlated to the dimensions of team cohesion. About 63% of team cohesion is explained by the imagery use dimensions. These dimensions are individual attraction- task team cohesion (39% of the variable), group integration-social team cohesion with 35% and group integration-task with 42%. The finding recommends cognitive and motivational elements from imagery use to be highlighted on team sports to promote athlete’s team cohesion.